The Influence of Human Resources Competence, Utilization of Accounting Information Systems, and Internal Control Systems: (Quality of Financial Statements with Transformational Leadership Style as a Moderation Variable in BMKG Bali Province) - Aniceta Ardyahayu Anggarari; Gregorius Paulus Tahu; I Made Dauh Wijana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The quality of government agency financial reports demonstrates accountability and transparency in public financial management, meeting the demands of good governance. This study aims to analyze the influence of human resource (HR) competency, the use of accounting information systems, and internal control systems on financial report quality, and to examine the role of transformational leadership as a moderating variable at the BMKG (Meteorology, Climatology, and Geophysics Agency) of Bali Province. This study employed a quantitative approach with a survey method. The population comprised all 75 financial and asset management employees at four BMKG work units in Bali Province. The sampling technique used saturated sampling, with all members serving as respondents. Primary data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) using SmartPLS software. The results of the study indicate that HR Competence has a positive and significant effect on the quality of financial reports, Accounting Information Systems do not affect the quality of financial reports, Internal Control Systems have a positive and significant effect on the quality of financial reports, Transformational Leadership Style has a positive and significant effect on the quality of financial reports, Transformational Leadership Style is unable to moderate the influence of HR and the use of accounting information systems on the quality of financial reports, and Transformational Leadership Style is proven to moderate the influence of internal systems on the quality of financial reports at the BMKG of Bali Province.